Concurrent chemoradiotherapy with S-1 versus platinum in the treatment of locoregionally advanced nasopharyngeal carcinoma: a multicenter, retrospective, propensity score-matched analysis - Bian, Chenbin; Zheng, Zhuangzhuang; Su, Jing; Chang, Sitong; Yu, Huiyuan; Bao, Jindian; Zhao, Qin; Jiang, Xin (Frontiers in Pharmacology, 2024)
Objectives Literature data are scarce on concurrent chemoradiotherapy (CCRT) with S-1 for locally advanced nasopharyngeal carcinoma (LANPC) treatment. This study compared the efficacy and safety of the S-1 versus platinum-based CCRT in LANPC treatment. Methods: This study enrolled 547 patients newly diagnosed with LANPC who underwent CCRT with S-1 or platinum at three institutions. Propensity score matching in a 1:1 ratio balancing baseline features was performed. Survival and adverse effects were compared between groups. Results Of 160 patients in the cohort, 100 eligible were propensity score matched. Matched dataset analyses showed a higher 5-year overall survival rate (87.1% vs. 84.7%, P = 0.833), progression-free survival (79.6% vs. 75.5%, P = 0.669), locoregional recurrence-free survival (87.0% vs. 84.7%, P = 0.518), and distant metastasis-free survival (84.8% vs. 83.0%, P = 0.780) in the S-1 group than in the platinum-based CCRT group, although not statistically significant. Objective response rate (98.0% vs. 88.0%, P = 0.117) was significantly higher in the S-1 than in the platinum-based regimen, although it was not statistically reflected. Compared with platinum-based, those undergoing S-1-based chemotherapy demonstrated a higher incidence of grade 3 mucositis (20.0% vs. 2.0%, P = 0.016) in the S-1 group and a lower incidence of leukopenia (44.0% vs. 68.0%, P = 0.033), neutropenia (28.0% vs. 52.0%, P = 0.032), anemia (22.0% vs. 44.0%, P = 0.040), nephrotoxicity (4.0% vs. 20.0%, P = 0.028), and nausea/vomiting (30.0% vs. 56.0%, P = 0.019). Conclusion The results suggest that S-1 can be used as a concurrent chemotherapy regimen during radiotherapy for patients with LANPC, since it presents a noninferior survival benefit compared with platinum and shows tolerable adverse effects.